(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The health risks associated with to biological wastes in the job description of hospital housekeepers are often overlooked. Hospital housekeepers are constantly being exposed to biological hazards, but their job risks are frequently disregarded. This study evaluated the prevalence, awareness, and frequency of biological risk exposure among hospital housekeepers in Oshimili South, Delta State, Nigeria. A structured questionnaire was used to conduct a cross-sectional survey of 120 randomly selected hospital housekeepers. Demographics, exposure to biological materials, use of personal protective equipments (PPE), health problems, and infection control training were all determined using descriptive statistics and Chi-square test. Majority of the respondents (54.2%) were females and between the ages of 31 to 40 (33.3%). Although, 85% were aware of biological dangers, only 50% had formal infection control training. Urine (76.7%), blood (73.3%), and faeces (69.2%) were the most common sources of exposure, with 56.7% of cases being accidental. Hand gloves usage was highest (86.7%) PPE known, but only 45% reported consistent PPE availability. Significant association were found between education level and awareness (x2 = 9.63, p = 0.008), exposure frequency and infection history (x2 = 10.25, p = 0.017), PPE availability and accidental exposure ( x2= 11.82, p = 0.009), as well as IPC training and infection history (x2 = 8.47, p = 0.037). There were no significant associations detected between gender and glove use, or marital status and symptom reporting. Targeted training and increased PPE access are critical for risk reduction among hospital housekeepers in the study area.